miR-100 induces epithelial-mesenchymal transition but suppresses tumorigenesis, migration and invasion. - Dahu Chen; Yutong Sun; Yuan Yuan; Zhenbo Han; Peijing Zhang; Jinsong Zhang; M James You; Julie Teruya-Feldstein; Min Wang; Sumeet Gupta; Mien-Chie Hung; Han Liang; et al. (PLoS Genetics, 2014)
Whether epithelial-mesenchymal transition (EMT) is always linked to increased tumorigenicity is controversial. Through microRNA (miRNA) expression profiling of mammary epithelial cells overexpressing Twist, Snail or ZEB1, we identified miR-100 as a novel EMT inducer. Surprisingly, miR-100 inhibits the tumorigenicity, motility and invasiveness of mammary tumor cells, and is commonly downregulated in human breast cancer due to hypermethylation of its host gene MIR100HG. The EMT-inducing and tumor-suppressing effects of miR-100 are mediated by distinct targets. While miR-100 downregulates E-cadherin by targeting SMARCA5, a regulator of CDH1 promoter methylation, this miRNA suppresses tumorigenesis, cell movement and invasion in vitro and in vivo through direct targeting of HOXA1, a gene that is both oncogenic and pro-invasive, leading to repression of multiple HOXA1 downstream targets involved in oncogenesis and invasiveness. These findings provide a proof-of-principle that EMT and tumorigenicity are not always associated and that certain EMT inducers can inhibit tumorigenesis, migration and invasion.